The Wiley-Blackwell handbook of infant development. Vol. 2 - Bremner, J. Gavin, 1949-; Wachs, Theodore D., 1941-; Wiley Online Library (Chichester, West Sussex : Wiley-Blackwell, 2010)
'Now in two volumes, the fully revised and updated second edition of The Wiley-Blackwell Handbook of Infant Development provides comprehensive coverage of the basic research and applied and policy issues relating to infant development. Updated, fully-revised and expanded, this two-volume set presents in-depth and cutting edge coverage of both basic and applied developmental issues during infancy. Features contributions by leading international researchers and practitioners in the field that reflect the most current theories and research findings. Includes editor commentary and analysis to synthesize the material and provide further insight. The most comprehensive work available in this dynamic and rapidly growing field.'--Provided by publisher.
Chapter 12: Genetic Disorders Associated with Intellectual Disability: An Early Development Perspective (Deborah J. Fidler, Colorado State University, Lisa Daunhauer, Colorado State University, David E. Most, Colorado State University, and Harvey Switzky, Northern Illinois University). -- Part IV: Intervention and policy issues. -- Chapter 13: Early intervention (Douglas R. Powell, Purdue University). -- Chapter 14: Childcare Research at the Dawn of a New Millennium: An update (Sarah L. Friedman, CNA, Edward Melhuish, Birkbeck, University of London, and Candace Hill, CNA). -- Chapter 15: Infancy research, policy, and practice (Marguerite Barratt and Erica Fener, The George Washington University).
Revised edition of: Blackwell handbook of infant development / edited by Gavin Bremner and Alan Fogel. 2001.
Includes bibliographical references and index.
Print version record; title from PDF of title page (Wiley Online Library, viewed Jan. 14, 2011).
Keywords: Infants -- Development -- Handbooks, manuals, etc; Infants -- Health and hygiene -- Handbooks, manuals, etc; Child development; Infant Care; Infant